Fabrication of an electrically-resistive, varistor-polymer composite - Ahmad @ Ayob, Mansor; Fatehi, Asma; Zakaria, Azmi; Mahmud, Shahrom; Abdolmohammadi, Sanaz (MDPI, 2012)
This study focuses on the fabrication and electrical characterization of a polymer composite based on nano-sized varistor powder. The polymer composite was fabricated by the melt-blending method. The developed nano-composite was characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FeSEM), and energy-dispersive X-ray spectroscopy (EDAX). The XRD pattern revealed the crystallinity of the composite. The XRD study also showed the presence of secondary phases due to the substitution of zinc by other cations, such as bismuth and manganese. The TEM picture of the sample revealed the distribution of the spherical, nano-sized, filler particles throughout the matrix, which were in the 10–50 nm range with an average of approximately 11 nm. The presence of a bismuth-rich phase and a ZnO matrix phase in the ZnO-based varistor powder was confirmed by FeSEM images and EDX spectra. From the current-voltage curves, the non-linear coefficient of the varistor polymer composite with 70 wt% of nano filler was 3.57, and its electrical resistivity after the onset point was 861 KΩ. The non-linear coefficient was 1.11 in the sample with 100 wt% polymer content. Thus, it was concluded that the composites established a better electrical non-linearity at higher filler amounts due to the nano-metric structure and closer particle linkages.